2000
DOI: 10.1161/01.cir.102.19.2378
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Atrioventricular Compliance on Pulmonary Artery Pressure in Mitral Stenosis

Abstract: Background-The decay of the pressure gradient across a stenotic mitral valve is determined by the size of the orifice and net AV compliance (C n ). We have observed a group of symptomatic patients, usually in sinus rhythm, characterized by pulmonary hypertension (particularly during exercise) despite a relatively large mitral valve area by pressure half-time. We speculated that this discrepancy was due to low atrial compliance causing both pulmonary hypertension and a steep decay of the transmitral pressure gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
126
3
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(137 citation statements)
references
References 35 publications
5
126
3
3
Order By: Relevance
“…In keeping with the findings of Boussuges et al (3), we also found alterations in transmitral flow on echo-Doppler with a decrease in the E/A ratio on ascent to high altitude, suggestive of a reduction in left ventricular diastolic compliance. A fall in diastolic compliance would increase the risk of developing pulmonary edema on exercise (45), and one may argue that some of the increase in EVLW seen in this study could be due to repeatedly elevated Ppc during physical activity. Nevertheless, the failure of the Poon analysis to demonstrate any relationship between either mean or systolic Ppa and either the changes in EIT or FVC, while demonstrating a strong relationship between the changes in EIT or FVC and NPD, argues against the subclinical pulmonary edema seen in this study being of predominantly hydrostatic origin.…”
Section: Discussionmentioning
confidence: 83%
“…In keeping with the findings of Boussuges et al (3), we also found alterations in transmitral flow on echo-Doppler with a decrease in the E/A ratio on ascent to high altitude, suggestive of a reduction in left ventricular diastolic compliance. A fall in diastolic compliance would increase the risk of developing pulmonary edema on exercise (45), and one may argue that some of the increase in EVLW seen in this study could be due to repeatedly elevated Ppc during physical activity. Nevertheless, the failure of the Poon analysis to demonstrate any relationship between either mean or systolic Ppa and either the changes in EIT or FVC, while demonstrating a strong relationship between the changes in EIT or FVC and NPD, argues against the subclinical pulmonary edema seen in this study being of predominantly hydrostatic origin.…”
Section: Discussionmentioning
confidence: 83%
“…Patients with low Cn were more symptomatic with symptoms corresponding to severe increases in pulmonary artery pressures during stress echocardiography. 11 Mitral stenosis is best described as a disease continuum, with no single value that can define its severity. More specifically, a wide variation in pulmonary pressures for the same range of mitral obstruction emphasizes the need to identify key factors implicated in the development of pulmonary hypertension and functional limitation in MS. 12 The presence of pulmonary hypertension is fundamental in the clinical decision-making process for mitral stenosis (MS).…”
mentioning
confidence: 99%
“…Moreover, right atrial pressure is frequently assumed to be 5 mm Hg in normal subjects 30 and 10 mm Hg in patients with heart disease. 31 Though we have demonstrated higher risk of functional mitral stenosis in patients receiving a Profile rigid ring, this cannot be generalized to all category or rigid rings; moreover, we cannot say whether or not this actually results in a poorer clinical outcomes or survival rate in the long run. Long-term follow-up data and more investigations are needed to address this issue.…”
Section: Limitationsmentioning
confidence: 81%